(untitled) (Bangladesh Pharmaceutical Journal, 2017)
The present study was conducted to evaluate the antipyretic, anti-inflammatory and membrane stabilizing, antioxidant, thrombolytic, anti-diarrheal activities of Scindapsu shederaceus belonging to the Araceae family. In antipyretic test, temperature reduced from 101.53°F to 99.86°F (p<0.05), 99.20°F (p<0.05) and 99.06°F (p<0.05) in 1st, 2nd and 3rd hour, respectively and caused maximum reduction of temperature in 1st hour. In the hot plate method, the extract increased the reaction time of heat sensation significantly to 14.32 seconds. In in vitro anti-inflammatory test, the extract significantly inhibited protein denaturation by 85.17% at 500 ?g/ml, 71.72% at 250 ?g/ml and by 66.55% at 125 ?g/ml. It also inhibited the hypotonic solution-induced haemolysis by 73.19%, 49.69% and 29.15% at same concentration in membrane stabilizing assay. In DPPH inhibition assay the extract showed maximum % inhibition of 65.5% at 100 ?g/ml. In the assay of thrombolytic activity, the extract showed thrombolytic activity of 14.39%. Amylase inhibitory activity was found to be 22.38% at a concentration 100 ?g/ml. In case of antidiarrheal investigation, the extract reveled total inhibition of defection by 35.30%. Bangladesh Pharmaceutical Journal 20(1): 85-89, 2017